PENGEMBANGAN INOVASI PENGAWETAN BAMBU SEBAGAI BAHAN KONSTRUKSI BANGUNAN DI DESA BELEGA, GINYAR, BALI - A.A. Gede Raka Gunawarman; I Wayan Wirya Sastrawan; Ni Luh Anik Puspa Ningsih (Lentera Karya Edukasi, 2022)
Abstract: Belega village is known as a center for bamboo craftsmen, especially furniture and interior decoration in Bali. The 90s were the heyday of the bamboo craftsmen in Belega Village who succeeded in exporting bamboo handicrafts to America, Europe, and several Asian countries. However, since the opening of the Ida Bagus Mantra bypass around 1998, tourist visits have begun to decrease and have resulted in a decline in furniture orders. The decline in orders for handicrafts caused some craftsmen to start switching to bamboo building construction in 2010. The method of implementing the service program began with the development of the production sector with a focus on bamboo preservation innovation. The field of management focuses on the implementation of administration specifically in problems that occur related to capital by providing socialization and assistance. Partners' participation in implementing this program is more about developing bamboo preservation ideas and innovations according to community needs and designing a marketing plan model with the team.Abstrak: Desa Belega dikenal sebagai pusat pengrajin bambu khususnya furniture dan hiasan interior di Bali. Tahun 90-an adalah masa jaya dari para pengrajin bambu di Desa Belega berhasil mengekspor hasil kerajinan bambu  ke Amerika, Eropa, dan beberapa negara Asia. Namun sejak dibukanya bypass Ida Bagus Mantra sekitar tahun 1998, kunjungan wisatawan yang mulai berkurang dan berdampak menurunnya pesanan furniture. Penurunan pesanan kerajinan menyebabkan beberapa pengrajin mulai beralih ke konstruksi bangunan bambu di tahun 2010. Metode pelaksanaan program pengabdian dimulai dengan pengembangan bidang produksi dengan fokus pada inovasi pengawetan bambu. Dalam bidang manajemen, berfokus pada pelaksanaan administrasi secara spesifik dalam permasalahan yang terjadi terkait permodalan dengan memberikan sosialisasi dan pendampingan. Partisipasi mitra dalam pelaksanaan program ini lebih kepada pengembangan ide dan  inovasi pengawetan bambu yang sesuai kebutuhan masyarakat dan rancangan model rencana pemasaran bersama tim.